The policy of Mansur Saif al-Din Qalawun towards the Crusader forces in the Levant - Duried Nory (آداب الرافدين, 1978)
As a result of the Crusader invasion of the Levant, Muslim rulers emerged who were able - with their ability and competence - to occupy the command center for the Levant region or some of its cities and to lead the united front that they formed from what they could unify from the countries of Egypt, the Levant and the countries of the Jazira, due to the weakness of the central authority in Baghdad. On the one hand, and the ability of these leaders to discover their own aspirations for unity and liberation, on the other hand. Therefore, it was not surprising that the leadership received from the rest of the Mamluks who could discover the goals of his people and work to achieve them. Masif al-Din Qalawun is only one of those leaders who looked deeply at the goals of their nation in confronting the Crusaders and liberating the Levant from important control and worked to achieve them as achieved by Nur al-Din Mahmud Zangi (d. 569 AH / 1174 CE) and Salah al-Din al-Ayyubi (18 AH / 1112 CE) ) Who, thanks to their confrontation of the Crusaders, gained the admiration of the Islamic nation. Whereas, fighting the Crusaders does not result in improvisational heroic action alone, but rather through unity and building the home front first, and preparing the waiting period again. Therefore, the subject of the research included two paragraphs, the first was about the policy that Qalawun pursued in order to build the home front, while the second paragraph included his position on the Crusaders and the steps he followed in stopping their attacks on the Levant and his military and diplomatic plans to repel that attack. I deliberately researched this topic because what I found in the Arab Library in terms of research in this section did not fulfill the required purpose, especially since researching the topic of the Crusades is considered an important topic, because the Arab nation today is still conquered from the colonial West, just as it was conquered by the Crusader West. . Therefore, studying the causes of the invasions that our nation faced previously, and getting acquainted with their positions And their solutions to them may be useful in shedding light on our contemporary problems and pushing us to identify the factors that enabled these leaders, including Saif al-Din Qalawun, to prevail over those invaders who were aiming to eliminate the Islamic presence in the Levant region, because one of the most important results of our study of history is to gain a lesson And benefit from it | In correcting present steps. The idea of ​​seeking the help of the Mamelukes appeared since the era of the Abbasid Caliph Al-Ma'mun, then Al-Mu'tasim sought help from them more often as he brought large teams of Turkmen to consolidate his power. And when the Ikhshidid state was established in Egypt, Muhammad bin Tughij made his army from the Turks and from Daylam, and when the power devolved to the Ayyubids, they bought more than the Turkish Mamluks until they became large numbers inside Egypt and they had their own advantages and their distinguished aristocracy in society.